Leaders as learners: developing new leadership practices. Issue 3 (27th May 2017) - Aas, Marit
Abstract : Professional learning and development of school leaders are considered keys to educational change. However, a growing body of research has identified how difficult it is to design professional leadership programmes that make a difference in leaders' professional practice. Drawing on the framework of expansive learning and data from the six-year National Principal Training Programme in Norway, a case study is presented as a narrative of the development of one principal to illuminate the process. This article demonstrates how leadership learning and development can occur through critical investigations of the school leaders' own leadership roles and practices. Reflections on the tensions revealed that 360-degree interviews, group coaching, theoretical studies and adopting the new leadership practice increase the leaders' metacognitive skills, self-awareness and context understanding, and motivation and confidence to transform their leadership practice. Professional development that is designed for a variety of opportunities for individual and collective reflections supports leaders to become learners with the capacity to make changes in their leadership practice, as well as in their school.